DEVELOPMENT OF PERSONNEL POTENTIAL IN ENSURING THE EFFICIENCY OF THE AGRICULTURAL ENTERPRISE - SOBCHYSHYN, Vitalii; SKUIBID, Vladyslav; DEREZA, Yuliia; MARKIN, Аnton (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article analyzes the main components of personnel potential. It has been proven that the main reason for the development of the personnel potential of the enterprise is to ensure its stability and long-term development under the conditions of market competition. It is substantiated that the development of personnel potential increases the decisive role in ensuring the efficiency of the enterprise. This is due to the fact that the success of the company largely depends on the quality of human resources, their competence, motivation and ability to adapt to new conditions. This includes continuous training and professional development of employees, which ensures the relevance of their knowledge and skills in the context of modern technological and market trends. Investments in training programs, training and the development of special skills help to increase productivity, reduce the number of errors and increase the quality of production products or services.In modern business conditions, domestic enterprises face the problem of finding highly qualified personnel. It is the personnel that determines the competitiveness of the organization, provides it with an economic and social advantage. And this is obvious, because the dependence of the final result of the activity on the involvement of intellectual and qualification potential in the labor process is clearly visible. The development of personnel potential is one of the most important areas of activity with personnel management and a factor in the effective operation of the enterprise. At the same time, investing in the development of personnel plays a greater role than investing in the development and improvement of production potential. The human resource management system of the enterprise should set before itself the task of planning and organizing the professional career of employees, on which the results of the entire enterprise depend, which, in the end, provides the possibility of increasing the human resource potential of the enterprise and is a condition for its development.
Keywords: personnel potential; modern technologies; professional development; agricultural enterprises; human resources; long-term development